Surface neatness as an index of aesthetic value of everyday objects - Tatiana Ledneva; Andriy Myachykov; Andriy Myachykov; Yury Shtyrov; Yury Shtyrov (Frontiers in Psychology, 2025)
IntroductionSurface neatness is a fundamental yet underexplored determinant of the aesthetic evaluation of everyday objects. While prior research has typically examined individual surface features - such as gloss, shine, dirt, or scratches - in isolation, the holistic impact of surface neatness has received little systematic attention.MethodsIn this study, participants viewed images of objects from five categories (household items, tools, personal use items, stationery, and kitchen utensils), each presented in three surface conditions: untidy (displaying mechanical and hygienic defects), neutral (without visible defects), and neat (exhibiting gloss and cleanliness). For each object, participants provided a preference rating reflecting their aesthetic evaluation.ResultsAnalysis revealed a robust effect of surface neatness on aesthetic preference: objects in the untidy condition consistently received the lowest ratings, while neat surfaces were rated most attractive. The differences between all surface conditions were statistically significant.DiscussionThese results demonstrate that surface neatness is a dynamic and salient factor shaping the perceived value and desirability of everyday objects. The findings underscore the need for more rigorous operationalization of surface properties in empirical research on human-object interaction and suggest practical applications for product design, consumer psychology, and sustainable practices, where surface conditions directly influence aesthetic experience and object appeal.